(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
Deposits of the Gzhelian-Asselian Stages were recognized by fusulinid occurrences in the upper part of the Sardar Formation (Zaladu Member) of the Ozbak Kuh region, East Iran. These deposits cannot be referred to the Bage-Vang Formation, which contains Bolorian fusulinids of the early Permian and lies at the base of a trangressive carbonate sequence. The results obtained in the Carboniferous-Permian section of East Iran are similar to those of western and southern Tethys. Everywhere the Asselian and, locally, the Sakmarian deposits are closely related to the Upper Carboniferous ones. After the late Sakmarian.Yakhtashian regression, carbonate platforms were formed from the Bolorian time through the Late Permian. The Zaladu Member contains 10 genera – Rauserites, Kushanella (?), Schellwieina, Anderssonites (?), Praepseudofusulina, Quasitriticites, Ruzhenzevites, Paraschwagerina, Pseudoschwagerina, Sphaeroschawagerina (?), and 37 species and subspecies of fusulinids. New species and subspecies are described: Rauserites infrequentis, R. tabasensis, R. fusoides, R. inobservabilis, R. (?) persicus, Quasitriticites iranicus, Ruzhenzevites zaladuensis zaladuensis, R. zalanduensis brevis, and R. ferganensis curtus.